Implementation of Deep Learning in the IPAS Subject at Islamic elementary school - Hidayah, Nailatul; Ramadhani, Fauziyah Asri; Nabila, Zaidatun; Assani, Kunti Fadilah; Rohmah, Umi; Fatimah, Siti; Fauziah, Muna; Arifah, Umi (Proceeding International Conference on Religion, Science and Education, 2026)
The purpose of this study is to analyze the implementation of deep learning in the IPAS (Integrated Natural and Social Sciences) subject at Madrasah Ibtidaiyah Al-Mukarromah. This research uses a qualitative approach with a phenomenological method. Data collection techniques include interviews, observation, and documentation. The data analysis technique uses the Miles, Huberman, and Saldana model, which consists of data condensation, data display, and data verification. The research findings show that the implementation of deep learning in the IPAS subject has applied the principles of conscious learning, meaningful learning, and joyful learning. IPAS learning also applies learning experiences, including understanding, applying, and reflecting. The obstacles faced in IPAS learning include limited time allocation, lack of technology-based facilities and infrastructure, and insufficient funds for teaching aids. The methods used in implementing deep learning include discussion, project-based learning, and problem-based learning.